Variation in habitat connectivity generates positive correlations between species and genetic diversity in a metacommunity. Issue 17 (11th July 2013) - Lamy, T.; Jarne, P.; Laroche, F.; Pointier, J.‐P.; Huth, G.; Segard, A.; David, P.
Abstract An increasing number of studies are simultaneously investigating species diversity (SD) and genetic diversity (GD) in the same systems, looking for 'species– genetic diversity correlations' (SGDCs). From negative to positive SGDCs have been reported, but studies have generally not quantified the processes underlying these correlations. They were also mostly conducted at large biogeographical scales or in recently degraded habitats. Such correlations have not been looked for in natural networks of connected habitat fragments (metacommunities), and the underlying processes remain elusive in most systems. We investigated these issues by studying freshwater snails in a pond network in Guadeloupe (Lesser Antilles). We recorded SD and habitat characteristics in 232 ponds and assessed GD in 75 populations of two species. Strongly significant and positive SGDCs were detected in both species. Based on a decomposition of SGDC as a function of variance–covariance of habitat characteristics, we showed that connectivity (opportunity of water flow between a site and the nearest watershed during the rainy season) has the strongest contribution on SGDCs. More connective sites received both more alleles and more species through immigration resulting in both higher GD and higher SD. Other habitat characteristics did not contribute, or contributed negatively, to SGDCs. This is true of the desiccation frequency of ponds during the dry season, presumably because species markedly differ in their ability to tolerate desiccation. Our study shows that variation in environmental characteristics of habitat patches can promote SGDCs at metacommunity scale when the studied species respond homogeneously to these environmental characteristics.